Primary Gastric Lymphoma- A Case Report (Journal of Medicine, 2015)
Primary gastric lymphoma accounts for less than 5% of gastric cancers. They are usually non-Hodgkinslymphomas (NHL), but have been considered as a separate entity from NHLs of peripheral nodes. The diagnosis of primary lymphoma of stomach requires histological confirmation without any evidence of peripheral lymphadenopathy or organomegaly. Secondary gastric lymphoma indicates the involvement of the stomach by a diffuse lymphoma developed elsewhere. Here we report a 50 year old male presented with abdominal pain and intermittent vomiting and diagnosed as primary gastric lymphoma.J MEDICINE July 2015; 16 (2) : 132-134